AXL Inhibition Extinguishes Primitive JAK2 Mutated Myeloproliferative Neoplasm Progenitor Cells. Issue 3 (June 2019) - Pearson, Stella; Blance, Rognvald; Somervaille, Tim C.P.; Whetton, Anthony D.; Pierce, Andrew
Abstract : Abstract: Myeloproliferative neoplasms (MPN) are clonal stem cell associated disorders inclusive of chronic myeloid leukemia (CML), Polycythaemia vera (PV), myelofibrosis (MF), and essential thrombocythemia (ET). They are characterized by increased production of myeloid cells with minimal effects on terminal differentiation but can undergo transformation to acute leukemias. PV is the most common chronic myeloproliferative neoplasm and in the majority of cases is characterized by a V617F point mutation in JAK2. This JAK2 activating mutation is also found in about half the patients with MF and ET. Such aberrant proteins offer great potential for the treatment of these diseases however inhibitors to JAK2 have had limited success in the clinic in terms of curing the disease. We have previously used advanced proteomic techniques to identify drug targets and thus develop novel treatment strategies to distinguish the leukemic clone in both CML and PV. Here, we build on our proteomic data sets to characterize a new target, the receptor tyrosine kinase AXL. AXL is overexpressed in acute myeloid leukemia and importantly small molecule inhibitors have been developed which are currently in clinical trial hence offer the opportunity to repurpose this drug for the treatment of MPNs. We demonstrate that AXL is upregulated and activated in JAK2 associated MPNs. Further we show that inhibition of AXL preferentially kills early hemopoietic stem cells from PV patients and as such represents a promising therapeutic approach for JAK2 driven MPNs. Abstract : Supplemental Digital Content is available in the text